Between Cost Cheap Prices And Increasing High Quality Educational University In Pekanbaru City - Widayat, Prama (Jurnal Penjaminan Mutu, 2018)
The need of higher education in the community has become the main thing for the future, not all can study at State Universities (PTN) but some must enter in Private Universities (PTS). But the problem that arises is the problem of tuition fees in the PTS course higher than the state university, the tendency of prospective students in choosing Higher Education (PT) based on cost and quality. While the problems from the PT side lies in the budget constraints in improving quality because of talk about the quality of course comprehensive from the means of lectures to the specialization of universities. Limitations of costs can at least be overcome by the synergy of universities, private companies and governments so it is not always student.